Edge irregular reflexive labeling on sun graph and corona of cycle and null graph with two vertices - Irfan Setiawan; Diari Indriati (Indonesian Combinatorial Society (InaCombS), 2021)
Let G(V,E) be a simple and connected graph which set of vertices is V and set of edges is E. Irregular reflexive k-labeling f on G(V,E) is assignment that carries the numbers of integer to elements of graph, such that the positive integer 1,2, 3,...,ke assignment to edges of graph and the even positive integer 0,2,4,...,2kv assignment to vertices of graph. Then, we called as edge irregular reflexive k-labelling if every edges has different weight with k = maxke,2kv. Besides that, there is definition of reflexive edge strength of G(V,E) denoted as res(G), that is a minimum k that using for labeling f on G(V,E). This paper will discuss about edge irregular reflexive k-labeling for sun graph and corona of cycle and null graph, denoted by Cn ⨀ N2 and make sure about their reflexive edge strengths.